(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2009)
Domestic partnership or civil union has passed in every country in the European Union, and in Japan and Canada. Why not in America? Because we are the only one that’s really Christian. It seems to me that the single biggest enemy to homosexuality is Christianity … Any self-respecting gay should be an atheist. And so I think it’s a battle worth fighting, not because I want to live behind a white picket fence and be faithful to a lover and both wear wedding rings – I think that’s stupid. We find everywhere a clear recognition of the same truth … because of a general recognition of this truth the question has seldom been presented to the courts … These, and many other matters which might be noticed, add a volume of unofficial declarations to the mass of organic utterance that this is a Christian nation … We find everywhere a clear recognition of the same truth … Religion, morality and knowledge [are] necessary to good government, the preservation of liberty, and the happiness of mankind. We are a religious people whose institutions presuppose a Supreme Being. We the People of the State of California, grateful to AlmightyGod for our freedom … The People of Connecticut acknowledging with gratitude, the good providence of God, in having permitted them to enjoy a free government ...